Formalization of correlational studies of water problems - Carreon Guillen Javier; García Lirios Cruz; Yaneth Quiroz Campas Celia; Alexander Vallejo Montoya Elías; Espinoza Morales Francisco; Hugo Meriño Córdoba Victor; Ysabel Martínez de Meriño Carmen; Vicente Ovalles Toledo Luiz; Judith Brito Carrillo Clara; Verstapp Bund Arger (Journal of Model Based Research, 2023)
A methodological note proposes formal structures for correlational studies of water problems. It emphasizes variable definition, confounding control, and reproducibility.
Keywords: Conformity